Effects of coronavirus disease 2019 on the incidence, mortality, and prognosis of ischemic stroke: a systematic review and meta-analysis - Yang, Xinyue; Zhu, Wenhao (Frontiers in Neurology, 2025)
ObjectiveThe objective of this study was to conduct a systematic review on the effect of coronavirus disease 2019 (COVID-19) on the incidence, mortality, and prognosis of ischemic stroke. The systematic review also ascertained the relationship between COVID-19 and the Trial of Org 10,172 in Acute Stroke Treatment (TOAST) typing of ischemic stroke, as well as the risk factors for ischemic stroke in patients with COVID-19.MethodsThe relevant literature between COVID-19 and ischemic stroke incidence, mortality, and prognosis up to January 2024 were systematically reviewed. Searches were carried out PubMed, Embase, Web of Science, and Cochrane databases. Utilizing the Meta-analysis of observational studies in epidemiology (MOOSE) declaration list, a systematic review and meta-analysis were carried out. Heterogeneity and publication bias were assessed.ResultsTwenty-one studies encompassed 505,864 participants across 13 countries. In total, 1.1% of patients with COVID-19 infection had an ischemic stroke (odds ratio [OR], 0.011; 95% confidence interval [CI], 0.007–0.017; p < 0.001). COVID-19 was related to in-hospital mortality (OR, 2.76; 95% CI, 1.90–4.02; p < 0.001), mortality 3 months following the beginning of an ischemic stroke (OR, 2.54; 95% CI, 1.80–3.58; p < 0.001), and modified Rankin scale (mRS) score ≤2 at hospital discharge (OR, 0.62; 95% CI, 0.54–0.72; p < 0.001). mRS ≤ 2 at 3 months after the onset of ischemic stroke did not show any correlation significantly with COVID-19 (OR, 0.67; 95% CI, 0.43–1.06; p = 0.086). Longer hospital stays (OR, 0.13; 95% CI, 0.06–0.20; p < 0.001) and increased incidence of large-artery atherosclerosis and small-vessel disease phenotypes of ischemic stroke were observed in patients with both COVID-19 and ischemic stroke (p < 0.05). In patients with COVID-19, ischemic stroke was substantially linked with hypertension, diabetes, hyperlipidemia, smoking, atrial fibrillation, coronary artery disease, chronic kidney disease, and chronic obstructive pulmonary disease (p < 0.05).ConclusionCOVID-19 is linked with increased incidence and mortality rates for ischemic stroke, as well as a worsening prognosis for the condition. With the data obtained from this study, targeted strategies to prevent and treat ischemic stroke in the context of the COVID-19 can be developed.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024524016, identifier: CRD42024524016.